CHANGE IN TESTOSTERONE LEVELS IN ENDOSCOPIC OPERATIONS ON THE PROSTATE GLAND - E. A. Efremov; S. Yu. Shekhovtsov; D. S. Merinov; A. O. Butov; Yu. V. Kastrikin; T. I. Garaev (Исследования и практика в медицине)
To date, there have been single studies showing a decrease in testosterone levels in patients as a result of urologic surgeries. It was found that a low level of testosterone has a negative impact on the physical and mental state of men. It was also found that a low level of testosterone increases the likelihood of postoperative complications.Purpose. Study the changes in testosterone levels in prostate plasma ablation.Patients and methods. 47 patients with benign prostatic hyperplasia who underwent plasma ablation of the prostate were examined. All patients were divided into 3 groups: Group I (14 patients) – patients with a normal preoperative level of testosterone (above 12 nmol/L), IIA group (17 patients) – patients with preoperative testosterone deficiency receiving HRT 2 weeks before surgery and during the entire period of postoperative follow-up and IIB group (16 patients) – patients with preoperative testosterone deficiency who did not receive therapy. In addition to standard general clinical examinations, all patients had a blood test for total testosterone, luteinizing hormone, sex hormone binding globulin. The level of free testosterone was calculated from the nomogram of Vermeulen, also testing was carried out using questionnaires AMS and IIEF-5.Results. The decrease in the level of testosterone as a result of the operation was noted in all patients. A month after the operation, none of the groups recorded a return of testosterone values to the original level. However, in the group of patients undergoing HRT, normalization of the testosterone level (12.1 nmol/L and more) was noted by 30 days. Also, early and late postoperative complications were assessed in all three groups. In the group of patients with testosterone deficiency who did not receive HRT, the number of complications was significantly higher. In the group of patients receiving HRT, there was an improvement in the general condition and erectile function, confirmed by the results of the AMS and IIEF-5 questionnaires.Conclusion. Performing plasma ablation of the prostate gland on a par with other methods of endoscopic surgery of the prostate gland leads to a significant decrease in the level of testosterone in the blood. Performing such operations against a background of testosterone deficiency adversely affects the clinical course of the early postoperative period, the development of complications and the general condition of the patient. Preoperative diagnosis and correction of testosterone deficiency is an important component that allows minimizing the number of risks and complications resulting from surgical interventions, as well as improving the quality of life and accelerating post-operative rehabilitation of patients.